Exploration of geometrical concepts involved in the traditional circular buildings and their relationship to classroom learning - Seroto, Ngwako (University of Limpopo (Turfloop Campus), 2006)
Traditionally, mathematics has been perceived as objective, abstract, absolute and universal subject that is devoid of social and cultural influences. However, the new perspective has led to the perceptions that mathematics is a human endeavour, and therefore it is culture-bound and context-bound. Mathematics is viewed as a human activity and therefore fallible. This research was set out to explore geometrical concepts involved in the traditional circular buildings in Mopani district of Limpopo Province and relate them to the classroom learning in grade 11 classes. The study was conducted in a very remote place and a sample of two traditional circular houses from Xitsonga and Sepedi cultures was chosen for comparison purposes because of their cultural diversity. The questions that guided my exploration were: • Which geometrical concepts are involved in the design of the traditional circular buildings and mural decorations in Mopani district of the Limpopo Province? • How do the geometrical concepts in the traditional circular buildings relate to the learning of circle geometry in grade 11 class? The data were gathered through my observations and the learners’ observations, my interviews with the builders and with the learners, and the grade 11 learners’ interaction with their parents or builders about the construction and decorations of the traditional circular houses. I used narrative configurations to analyse the collected data. Inductive analysis, discovery and interim analysis in the field were employed during data analysis. From my own analysis and interpretations, I found that there are many geometrical concepts such as circle, diameter, semi-circle, radius, centre of the circle etc. that are involved in the design of the traditional circular buildings. In the construction of these houses, these concepts are involved from the foundation of the building to the roof level. All these geometrical concepts can be used by both educators and learners to enhance the teaching and learning of circle geometry. Further evidence emerged that teaching with meaning and by relating abstract world to the real world makes mathematics more relevant and more useful.
Thesis (M.Ed. (Mathematics)) --University of Limpopo, 2013
Keywords: Mathematics social influences; Mathematics cultural influences; Pedi architecture; 516.36; Social sciences -- mathematics; Architecture, Primitive